N2 influences on CH4 accumulation and displacement in shale by molecular dynamics - Jiawei Li; Yue Lang; Binhui Li; Yong Liu; Zhejun Pan; Sheikh S. Rahman (Scientific Reports)
Abstract N2 is generally employed as a displacement agent to enhance gas recovery in shale gas-bearing reservoirs. However, the primary displacement mechanism in the subsurface still needs to be clarified due to the characteristics of shale reservoirs with low porosity and abundant nanopores. This study employs the Molecular Dynamics (MD) simulation method to investigate the effects of N2 on the CH4 accumulation and displacement processes by adopting practical conditions in the subsurface environment. In equilibrium MD simulation processes, including the N2 from outside and inner kerogen matrix, keeping the gas ratio of 1:3 for CH4 and N2, the displacement is 52.4% and 65.3%, respectively, which suggests that CH4 cannot be entirely displaced by surrounding N2 particles, owing to the strong interaction between CH4 and the kerogen matrix. For the straightforward displacement process by N2, the displacement efficiency is enhanced by 71.7% at the 1:1 gas ratio. Another case of N2, in which generation is accompanied by displacement processes, at the ratio 1:2 for N2:CH4, shows a 47.1% displacement efficiency. This work evidences that the straightforward displacement process is more efficient on CH4 displacement, which enhances CH4 production at a pronounced scale and sheds light on the N2 displacement process in industrial shale gas reservoir production.